Schematic Brief Discussion on Bulimia Nervosa: A Psychiatric Disorder and Its Medical Management - Yash Srivastav; Sajjad Alam (Medicine and Medical Research: New Perspectives Vol. 3, 2024)
The primary objective of the study is to address any dietary issues and modify your behaviour. The relationship between your thoughts, feelings, and behaviours is examined in therapy. The disease known as bulimia nervosa, which is typified by purging and binge eating, usually starts in adolescence and peaks at the age of 18. Radioactive ligands are used in positron emission tomography (PET) and single photon emission computed tomography (SPECT) to investigate the distribution of neurotransmitter receptors and glucose metabolism. The ratio of female to male patients varies from 10:1 to 20:1, with a lifetime frequency of 3 per cent. The majority of bulimic individuals also suffer from other mental illnesses, such as depression or anxiety. Additionally, there is a correlation between substance misuse and promiscuity. Bulimia nervosa was initially identified as a "chronic phase of anorexia nervosa" in 1979 by British psychiatrist Gerald Russell. The main goal of treatment is to get the patient to stop bingeing and purging. It has been demonstrated that selective serotonin reuptake inhibitors, like sertraline, citalopram, and fluoxetine, lessen bulimia nervosa symptoms. During this stage, patients overeat and resort to compensatory methods such as self-induced vomiting, laxatives, or extended periods of deprivation. Episodes of bingeing and purging that happen at least once a week for three months are usually linked to a diagnosis of bulimia. Even sometimes engaging in purging and bingeing can be hazardous and necessitate medical treatment. The more often the episodes occur, the worse the bulimia gets. To treat bulimia, family therapy and individual treatment are commonly employed. We go over the aetiology, epidemiology, current treatment, and state of bulimia nervosa in this review study. Future counseling-based research in our nation or state will evaluate patients’ physical and mental health and generate more precise data on bulimia nervosa and its treatment, thanks to the assistance of our colleagues.